2018
DOI: 10.3390/ijms19061746
|View full text |Cite
|
Sign up to set email alerts
|

The “Magnesium Sacrifice” Strategy Enables PMMA Bone Cement Partial Biodegradability and Osseointegration Potential

Abstract: Poly (methyl methacrylate) (PMMA)-based bone cements are the most commonly used injectable orthopedic materials due to their excellent injectability and mechanical properties. However, their poor biocompatibility and excessive stiffness may cause complications such as aseptic implant loosening and stress shielding. In this study, we aimed to develop a new type of partially biodegradable composite bone cement by incorporating magnesium (Mg) microspheres, known as “Mg sacrifices” (MgSs), in the PMMA matrix. Bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…It was reported that the addition of additives into PMMA bone cements would decrease the mechanical property [32,33]. In our group’s previous study, the compressive strength also decreased with addition of magnesium balls [33]. This study shows the same results with previous reports.…”
Section: Discussionsupporting
confidence: 89%
“…It was reported that the addition of additives into PMMA bone cements would decrease the mechanical property [32,33]. In our group’s previous study, the compressive strength also decreased with addition of magnesium balls [33]. This study shows the same results with previous reports.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the addition of COL-I or LDH may alleviate stress-shielding osteolysis and indirectly promote osseointegration. 9,42 The Evaluation of Biocompatibility In Vivo and In Vitro. On the basis of the superior physical-chemical properties, the biocompatibility of the PMMA, PMMA&COL-I, PMMA&LDH, and PMMA&COL-I&LDH groups in vitro was further studied using human bone marrow-derived mesenchymal stem cells (hBMSCs).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, fluorescent labeling (Figure 5e,f) and acid fuchsin stain assays (Figure 5g,h) were utilized to analyze the degree of bone growing into the implants, and the results are similar to that of micro-CT. All the results indicate that LDH and COL-I&LDH-modified PMMA can be used as effective biomaterials to enhance the osseointegration of the interface between the bone and bone cement, and possibly prevent the occurrence of aseptic loosening. 9…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium phosphate-based bone cements have a wide range of medical applications as synthetic bone substitutes because of remarkable properties, such as self-aligning ability, high initial strength, biocompatibility, excellent adhesion, and degradability [58,66,67]. Besides, other researchers have emphasized that these materials are promising for bone replacement, in accordance with the degradability and ability to regenerate bone in orthopedic sheep implant models [68].…”
Section: Magnesium Phosphate-based Bone Cementsmentioning
confidence: 99%